Platelet Adhesion, Release and Aggregation in Flowing Blood: Effects of Surface Properties and Platelet Function. - Baumgartner, Hans R; Muggli, Reto; Tschopp, Thomas B; Turitto, Vincent T (Thrombosis and Haemostasis, 1976)
Platelet adhesion to natural and artificial surfaces and adhesion-induced aggregation were investigated in vitro using an annular perfusion chamber. The surfaces were exposed to anticoagulated blood under identical flow conditions (~ arterial shear rates). The initial attachment of platelets (contact) appeared less surface specific than spreading and release. Fibrillar collagen was the most powerful inducer of platelet degranulation whereas elastin, microfibrils and epon were virtually inactive. Fibrillar collagen caused release also in the absence of spreading. Surface coverage with platelets did not exceed 25 % unless spreading occurred. Perfusion with platelet-free plasma or platelet-poor blood did not remove adhering platelets. However, platelets were translocated from mural thrombi to the surface by such perfusion. In addition, platelets which detached from mural thrombi adhered more readily to elastin or microfibrils than platelets from the circulating blood. The initial attachment of platelets to subendothelium was inhibited in von Willebrand’s disease, the Bernard-Soulier syndrome and at high concentrations of dipyridamole; spreading was inhibited in storage pool disease of rats, at low temperature (20° C), with EDTA (3 mM) and Prostaglandin E1 (1 μM); and adhesion-induced aggregation was inhibited in thrombasthenia, storage pool disease and after ingestion of sulfinpyrazone or Aspirin.It is concluded that the initial attachment (contact) of platelets, spreading and surface-induced release of platelet constituents are at least partially independent phenomena, the latter two being highly surface specific. At flow conditions which cause the disappearance of platelet thrombi, platelet adhesion appears as an irreversible process.